PMO-154 Plasma HBSAG levels decline was similar during subsequent pegylated interferon and nucleos(T)IDE analogues treatment in chronic hepatitis B patients. (28th May 2012) - Bruce, M J; Horner, M; Hughes, S; Knighton, S; Joshi, D; Harrison, P M; Agarwal, K; Carey, I
Abstract : Introduction: Pegylated interferon (Peg-IFN) therapy responses in chronic hepatitis B (CH-B) are associated with decline of HBsAg plasma levels (qHBsAg) (>10% in HBeAg− and >0.5 log10 IU/ml in HBeAg+) and HBV DNA decrease >2 log10 IU/ml during the first 6 months of therapy. In contrast, qHBsAg decline is less pronounced, but with sharper HBV DNA decline on therapy with nucleos(t)ide analogues (NA). The previous studies comparing qHBsAg and HBV DNA kinetics between Peg-IFN and NA treatments were performed on variable cohorts, but not on a monocentric single cohort of patients undergoing consecutively variable courses of therapy. Aims: To compare the kinetics of qHBsAg and HBV DNA levels before and during therapy; initially with Peg-IFN and then after at least a 6-month break (median 15 months) with subsequent NA therapy in the same cohort of CH-B patients. Methods: qHBsAg levels by Abbott ARCHITECT® assay and HBV DNA by real-time TaqMan PCR [both log10 IU/ml] were quantified in serial samples at baseline, treatment week 12 (TW12), TW24, TW48. HBeAg loss/anti-HBe seroconversion were evaluated at the same time-points. All results are presented as medians. Results: Four Peg-IFN patients (20%) achieved anti-HBe seroconversion, in contrast to only 1 NA patient (5%). At baseline, qHBsAg and HBV DNA levels were similar between Peg-IFN and NA (3.92 vs 3.72 and 6.21 vs 5.91). At TW12 and TW24, qHBsAg did not change in Peg-IFN and NA treatment (3.86 vs 3.68 and 3.57 vs 3.49 respectively), but HBV DNA dropped significantly during NA therapy only (4.55 vs 2.29 and 4.53 vs 1.23, both p<0.01). At TW48, qHBsAg remained unchanged in both treatments (3.48 vs 3.46), but HBV DNA was undetectable in NA patients (0 vs 4.68, p<0.01). Only NA therapy achieved complete virological response (HBV DNA<20 IU/ml) in six patients (30%) at TW12, 8 patients (40%) at TW24 and 15 patients (75%) at TW48 (all p<0.05). Only patients with qHBsAg decline by >0.5 log10 IU/ml by TW24 achieved anti-HBe seroconversion in both treatments. Conclusion: HBsAg decline >0.5 log10 IU/ml by TW24 was predictive of anti-HBe seroconversion irrespective of therapeutic approach. Although plasma HBsAg kinetics was similar during Peg-IFN or NA therapy in Peg-IFN non-responders, HBV DNA viral load declined significantly only during NA therapy from TW12 in the same cohort of CH-B patients. Competing interests: M Bruce: None declared, M Horner: None declared, S Hughes: None declared, S Knighton: None declared, D Joshi: None declared, P Harrison: None declared, K Agarwal: None declared, I Carey grant/research support from: BMS, Gilea.